Innovations in bio-inspired computing and applications : proceedings of the 9th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2018) Held in Kochi, India During December 17-19 2018 /: proceedings of the 9th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2018) Held in Kochi, India During December 17-19 2018. ([2019]) - Unknown
No abstract available